The association between gut microbiome and anthropometric measurements in Bangladesh. (2nd January 2020) - Osborne, Gwendolyn; Wu, Fen; Yang, Liying; Kelly, Dervla; Hu, Jiyuan; Li, Huilin; Jasmine, Farzana; Kibriya, Muhammad G; Parvez, Faruque; Shaheen, Ishrat; Sarwar, Golam; Ahmed, Alauddin; et al.
ABSTRACT: Our objective was to investigate the relationship between the gut microbiota and anthropometric measurements among 248 participants from the Health Effects of Arsenic Longitudinal Study (HEALS) in Bangladesh. Our cohort represents a unique population that allows for the investigation of the gut microbiota and anthropometric measurements in lean individuals. We measured height, weight, arm, thigh, hip, and waist circumferences, and collected fecal samples. Microbial DNA was extracted from the stool samples and sequenced by 16S rRNA gene sequencing. We examined associations between relative abundance of individual bacterial taxa from phylum to genus levels and anthropometric measurements. We found that higher BMI, mid-upper arm circumference, waist circumference, and waist-to-hip ratio were associated with a lower alpha diversity of fecal bacteria. Relative abundance of the genus Oscillospira and the family S24-7 were inversely related to all measurements after correction for multiple testing. Relative abundance of genus Acidaminococcus and family Ruminococcaceae were also associated with several measurements. The positive associations of the genus Acidaminococcus with BMI, as well as waist and hip circumferences, were stronger in women than in men. Our data in this lean Bangladeshi population found a correlation between Oscillospira and leanness, as measured using multiple anthropometric measures.